As políticas públicas de planejamento e o desenvolvimento urbano de Uberlândia (MG) - Silva, João Paulo Gomes da (2014)
In Brazil the cities grew, in general, in an expedited manner and margin of legal regulations. This kind of occupation of urban land planning initiatives associated with poorly integrated, eventually negatively influence the urban infrastructure, impacting on quality of life. Urban planning is institutionalized in Brazil in the mid -1960s, while most urban problems was already consolidated. Thus, public policy planning, emerged as an attempt by the state to reverse this crisis. The new legal and administrative framework, assembled from the 1988 constitution, municipal governments provided legal instruments to act more forcefully on the property, so as to regulate the real estate market, aiming to reduce the cost of housing and at the same time, extend fundraising to finance urban infrastructure. In this sense, the master plan constitutes the main planning instrument for a city and serves as the basis for its management. Given this context, the research sought to understand the role of public policies in urban development planning of Uberlândia well as its spatial structure. We attempted to discuss how the city planning law, particularly the master plans of 1994 and 2006 influenced the actions of municipal government in recent years and consequently, the current configuration of urban space in the city of Uberlândia. Results pointed out that actions to order the urban space through Master Plans go beyond a constitutional obligation, also being a political, economic and cultural strategy, which aims to impose the need for intervention in space as an attempt to legitimize the city project proposed as a more coherent and viable.